2020
DOI: 10.3390/jcm9041002
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigms of Extended Thromboprophylaxis in Medically Ill Patients

Abstract: Extended thromboprophylaxis given to medically ill patients for up to 45 days following an acute hospitalization remains an emerging topic among many hospital-based health care providers. Recent advancements in the field of extended thromboprophylaxis using risk stratification and careful patient selection criteria have led to an improved safety profile of direct oral anticoagulants (DOACs) and established net clinical benefit when given to key patient subgroups at high risk of venous thromboembolism (VTE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
14
0
2
Order By: Relevance
“…Routine use of extended thromboprophylaxis after discharge without individualized risk assessment is not recommended [9]. A recent publication in this VTE series explores the recent trials for extended VTE prophylaxis and suggests an algorithm to determine which patients may benefit from extended prophylaxis [135].…”
Section: Medical Hospitalizationmentioning
confidence: 99%
“…Routine use of extended thromboprophylaxis after discharge without individualized risk assessment is not recommended [9]. A recent publication in this VTE series explores the recent trials for extended VTE prophylaxis and suggests an algorithm to determine which patients may benefit from extended prophylaxis [135].…”
Section: Medical Hospitalizationmentioning
confidence: 99%
“…It is known that the risk of hospital-associated VTE extends for up to 6 weeks post-discharge in medically ill patients with a high VTE risk, as those with pneumonia, sepsis and post-ICU admission [ 114 ], but the efficacy and safety of extended thromboprophylaxis in COVID-19 patients is still unclear [ 115 , 116 ]. Extended prophylaxis with LMWH or DOAC may be considered in patients with a high VTE and a low bleeding risk [ 10 , 102 , 117 ].…”
Section: Prophylaxismentioning
confidence: 99%
“…Most studies indicated positive health outcomes for those who took rivaroxaban, but some negative and some nonsuperior effects were also found. The FDA approved rivaroxaban to prevent VTE in acutely ill patients in October 2019, and based on this approval, rivaroxaban can be initiated during hospitalizations and continued for 31-39 days [ 35 ]. In the systematic review and meta-analysis comparing prolonged thromboprophylaxis with factor Xa inhibitors to the short-term enoxaparin, DOACs were more effective than enoxaparin but were also associated with more bleeding episodes [ 36 ].…”
Section: Venous Thromboembolism Prophylaxis In Acute Medical Illnementioning
confidence: 99%
“…The use of rivaroxaban in AF was also associated with a higher risk of bleeding in AF patients on hemodialysis in a systemic review of the randomized trials, cohort studies, and case series [ 60 ]. Rivaroxaban was not studied in the treatment or prophylaxis of DVT/PE in patients with CrCl < 30 mL/min, while the reduced dose of 2.5 mg twice daily was not tested in patients with CrCl < 15 mL/min [ 16 , 17 , 30 , 31 , 35 ]. Rivaroxaban is not recommended for the treatment of DVT/PE if CrCl is <30 mL/min, while the 2.5 mg twice daily dose should be used with caution in coronary artery disease and peripheral artery disease with CrCl 15-30 mL/min and is not recommended in ESRD [ 16 , 17 , 30 , 31 , 35 ].…”
Section: Consideration In Kidney Diseasementioning
confidence: 99%